2008
DOI: 10.1158/1078-0432.ccr-07-1354
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Food and Drug Administration Approval: Panitumumab for Epidermal Growth Factor Receptor–Expressing Metastatic Colorectal Carcinoma with Progression Following Fluoropyrimidine-, Oxaliplatin-, and Irinotecan-Containing Chemotherapy Regimens

Abstract: Purpose: To describe the Food and Drug Administration review and marketing approval considerations for panitumumab (Vectibix) for the third-line treatment of patients with epidermal growth factor receptor^expressing metastatic colorectal carcinoma. Experimental Design: Food and Drug Administration reviewed a single, open-label, multicenter trial in which 463 patients with epidermal growth factor receptor^expressing metastatic colorectal cancer who had progressed on or following treatment with a regimen contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 9 publications
1
43
0
5
Order By: Relevance
“…Current regimens for patients with metastatic CRC include anti-EGFR monoclonal antibodies such as cetuximab and panitumumab, both functioning to block the binding of ligands to EGFR, thereby downregulating ERK/MAPK and PI3K/PTEN/AKT pathway signalling (Amado et al, 2008;Giusti et al, 2008;Segal and Saltz, 2009). New evidence suggests that patients with KRAS, BRAF or PTEN mutations experience fewer clinical responses to these drugs, compared with patients with wild-type tumours; moreover, molecular analysis, particularly of KRAS, is routinely being performed in standard molecular pathology laboratories (Lievre et al, 2006;Amado et al, 2008;Di Nicolantonio et al, 2008;Karapetis et al, 2008;Au et al, 2009;Jimeno et al, 2009;Sartore-Bianchi et al, 2009).…”
mentioning
confidence: 99%
“…Current regimens for patients with metastatic CRC include anti-EGFR monoclonal antibodies such as cetuximab and panitumumab, both functioning to block the binding of ligands to EGFR, thereby downregulating ERK/MAPK and PI3K/PTEN/AKT pathway signalling (Amado et al, 2008;Giusti et al, 2008;Segal and Saltz, 2009). New evidence suggests that patients with KRAS, BRAF or PTEN mutations experience fewer clinical responses to these drugs, compared with patients with wild-type tumours; moreover, molecular analysis, particularly of KRAS, is routinely being performed in standard molecular pathology laboratories (Lievre et al, 2006;Amado et al, 2008;Di Nicolantonio et al, 2008;Karapetis et al, 2008;Au et al, 2009;Jimeno et al, 2009;Sartore-Bianchi et al, 2009).…”
mentioning
confidence: 99%
“…The efficacy of the drug in monotherapy has been demonstrated in comparison with best supportive care (BSC) in 463 mCRC patients refractory to 5-FU, irinotecan and oxaliplatin. In this trial, although no improvement in OS was obtained, panitumumab provided a significant benefit in RR (10 vs 0%; p < 0.001) and PFS at 8 weeks (49 vs 30%; p < 0.001) and further analysis confined these benefits to KRAS wild-type patients [65,66]. The use of panitumumab as first-line treatment in addition to FOLFOX chemotherapy has been evaluated in the randomised PRIME trial, the results of which showed an improvement both in median PFS for KRAS wild-type mCRC patients treated with panitumumab plus chemotherapy (10 vs 8.6 months; HR: 0.80; p = 0.01) and in median OS (23.9 vs 19.7 months; HR: 0.88; p = 0.17) [67].…”
Section: Anti-egfr (Cetuximab Panitumumab)mentioning
confidence: 66%
“…Three studies were excluded from the analysis: one study used an egfri in both arms 13 , one did not present rash rates according to either grades 3 and 4 criteria or allgrades criteria 14 , and one study was a duplicate of another study 15 . Thus thirteen studies were eligible for inclusion in the meta-analysis ( Table ii).…”
Section: Resultsmentioning
confidence: 99%